The Iconography of Family Members in Egypt's Elite Tombs of the Old Kingdom - Wen, Jing, (Biblical Studies, Ancient Near East and Early Christianity E-Books Online, Collection 2023., 2023)
In The Iconography of Family Members in Egypt's Elite Tombs of the Old Kingdom, , Jing Wen offers a comprehensive survey of how ancient Egyptians portrayed their family members in the reliefs of an elite tomb. Through the analysis of the depiction of family members, this book investigates familial relations, the funerary cult of the dead, ancestor worship, and relevant texts. It provides a new hypothesis and perspective that would update our understanding of the Egyptian funerary practice and familial ideology. The scenes of family members are not a record of family history but language games of the tomb owner that convey specific meaning to those who enter the chapel despite time and space.